What drives differences in preferences for health states between patients and the public? A qualitative investigation of respondents' thought processes. (August 2021) - Goodwin, Elizabeth; Davey, Antoinette; Green, Colin; Hawton, Annie
Abstract: Cost-effectiveness analyses using quality-adjusted life-years (QALYs) are used in decision-making regarding which interventions are available via many national healthcare systems. QALYs are calculated based on health state values provided by preference elicitation techniques. Several national decision-making bodies recommend that health state values should be based on preferences elicited from general populations, rather than from patients. Previous studies have shown systematic differences between health state values elicited from members of the general population and from patients. Various explanations for this phenomenon have been proposed, however empirical evidence for these is scarce. We aimed to explore possible reasons for discrepancies between public and patient valuations by undertaking qualitative cognitive interviews, asking 14 members of the general population and 12 people with multiple sclerosis (MS) to think aloud while completing a preference elicitation task (time trade-off) for MS-related health states. The interviews were undertaken between December 2016 and October 2017 in the South West region of England, and were analysed using the Framework Method. As anticipated, we found that participants with MS had more experience of health problems and used this experience to consider how they might adapt to the health states over time, and which dimensions of health-related quality of life were most important to them. We found no evidence that participants with MS were less affected by framing effects and focusing illusions, more likely to prioritise non-physical dimensions of health, or more prone to loss aversion, endowment effects and non-compensatory decision-making. These findings contribute to our understanding of how patients and members of the general population respond to preference elicitation exercises, and why their preferences may differ, and may help to inform developing areas of research, such as the joint presentation of cost-effectiveness results from multiple perspectives, and the use of preferences elicited from patients for experienced health states. Highlights: Patients' preferences for health states differ from those of the general population. We used think-aloud interviews to explore how people value health states. Patients were more likely to draw on their own experience and anticipate adaptation. These differences were less marked for older members of the general population. Our findings did not reflect other suggested reasons for differences in preferences.